2004
DOI: 10.1111/j.1550-7408.2004.tb00539.x
|View full text |Cite
|
Sign up to set email alerts
|

Parasites and Phytoplankton, with Special Emphasis on Dinoflagellate Infections1

Abstract: ABSTRACT. Planktonic members of most algal groups are known to harbor intracellular symbionts, including viruses, bacteria, fungi, and protozoa. Among the dinoflagellates, viral and bacterial associations were recognized a quarter century ago, yet their impact on host populations remains largely unresolved. By contrast, fungal and protozoan infections of dinoflagellates are well documented and generally viewed as playing major roles in host population dynamics. Our understanding of fungal parasites is largely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(50 citation statements)
references
References 91 publications
(164 reference statements)
3
47
0
Order By: Relevance
“…Abrupt declines in A. fundyense host abundance were observed following peaks in parasite prevalence. Similar impacts from parasites have been observed for other dinoflagellate blooms (e.g., Park et al, 2004; Chambouvet et al, 2008). …”
Section: Discussionsupporting
confidence: 77%
“…Abrupt declines in A. fundyense host abundance were observed following peaks in parasite prevalence. Similar impacts from parasites have been observed for other dinoflagellate blooms (e.g., Park et al, 2004; Chambouvet et al, 2008). …”
Section: Discussionsupporting
confidence: 77%
“…Also, according to network analysis, five out of the six most connected MALV-related OTUs (closely affiliated to MALV-II) were mostly connected with OTUs affiliated to dinoflagellates (e.g., Gyrodinium spp., Warnowia sp., Lessardia elongata). Planktonic dinoflagellates in general and the ones of the genus Gyrodinium in particular are infected by Syndiniales (e.g., Coats et al, 1996;Coats, 1999;Park et al, 2004). The genus Gyrodinium was represented by 42 OTUs of which 9 were abundant (>0.1%), and was always present in the samples and particularly abundant during spring and summer.…”
Section: Bolidomonas Pacifica (98%) [Ocean Waters]mentioning
confidence: 99%
“…Although dinoflagelllate cells have been found to contain multiple 18S rRNA gene copies, thus potentially affecting abundance data by oversaturating the sequencing samples (Stoeck et al, 2010;Pirreda et al, 2016), our microscope observations of the samples confirmed the overall dominant presence of Gyrodinium species. To date, the phenomenon of massive killing of dinoflagellates by MALV (e.g., Coats et al, 1996;Park et al, 2004;Guillou et al, 2008) has been the subject of scientific interest as a possible means to limit toxic dinoflagellate blooms . In addition, according to the overall connections of MALV-related OTUs as revealed by network analysis (Figure 6A), a larger host range and variability than previously thought was indicated, as MALVs are highly connected to diatoms (e.g., Rhizosolenia setigera, Minidiscus sp.…”
Section: Bolidomonas Pacifica (98%) [Ocean Waters]mentioning
confidence: 99%
“…Amoebophrya spp. infect and kill a taxonomically broad variety of dinoflagellates, including harmful algal bloom (HAB) species within the genera Alexandrium , Dinophysis , Karlodinium and Akashiwo [3]. During their life-cycle, Amoebophrya alternates between a free-swimming infective stage (dinospore) and a multinuclear growth phase (trophont) within its host [4], [5].…”
Section: Introductionmentioning
confidence: 99%